Resilience of a Banana Chips MSME Through Traditional Marketing in the Digital Era - Hariyani, Tuwis; Sari, Rini Ratna Nafita (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to analyze how a micro, small, and medium enterprise (MSME) can sustain its business operations without utilizing digital marketing in the era of digital transformation. The research focuses on a banana chips MSME located in Ngadiluwih Village, Ngadiluwih District, Kediri Regency, East Java, Indonesia, which has been operating since 2004 and continues to run smoothly despite limited digital literacy and human resources. A qualitative approach with a case study method was employed, involving in-depth interviews, direct observation, and documentation of the business owner’s practices. The findings reveal that business resilience is achieved through the implementation of traditional marketing strategies, such as word-of-mouth promotion, maintaining loyal customer networks, and direct participation in local markets. These strategies not only maintain stable daily sales but also strengthen social relationships between producers and consumers. The study concludes that MSME success without digitalization can be achieved by leveraging social relations and customer trust as key assets. The implications suggest the need for policy support and digital literacy training to help MSMEs gradually adapt to digital tools while preserving their established local strengths